Surgical treatment of type-II choledochal cyst: a case report - Zarco Arreola, Karla I.; Olvera Casas, Aldo; Bueno Vázquez, Luis J.; Huitzil Palafox, Selene Y. (International Journal of Research in Medical Sciences, 2022)
Choledochal cyst is a pathology conditioned by a complex congenital malformation that involves different degrees of dilation of both the common bile duct and the pancreatic duct with a malignant tendency, these are reported more frequently in children, representing 1% of benign diseases of the biliary. Babbitt ’s theory is the most frequently proposed theory and states that CCs (choledochal cysts) result from an anomalous pancreatobiliary junction (APBJ) where the pancreatic duct and bile duct connect 1-2 cm proximal to the sphincter of Oddi. In adults, the presentation is usually nonspecific and vague, with abdominal pain being the most common symptom. Surgical resection of cysts can significantly decrease the risk of malignancy and reduce associated complications. However, less attention has been paid to CC in adults, and its surgical parameters have been reported to be frequently controversial. This manuscript describes the clinical case of a Todani II choledochal cyst managed with surgical resection by laparotomy with Roux-en-Y biliodigestive reconstruction, obtaining satisfactory results.